2023
DOI: 10.16899/jcm.1210766
|View full text |Cite
|
Sign up to set email alerts
|

Femur Kırığı Olan Hastalarda Prognostik Nutrisyon İndeksi İle Mortalite Arasındaki İlişkinin Araştırılması

Abstract: Aim: The incidence of adverse postoperative outcomes in surgeries for femur fractures is high and is associated with malnutrition. In this study, it was aimed to determine the independent factors for 6-month survival in patients with femur fracture and to evaluate the predictive value of the prognostic nutrition index (PNI). Material and Method: One hundred and sixteen patients operated on only for femoral fracture were divided into survival and non-survival groups according to mortality.Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…PNI, when used as a preoperative pretest, can help predict postoperative mortality as a tool for evaluating nutrition. Taskin et al [ 19 ] reported that in geriatric femur fractures, preoperative albumin, prealbumin, and PNI values were found to be significantly lower in patients who developed mortality compared to those who survived. The authors stated that the cut-off PNI value for predicting mortality in patients with femur fractures was 29, and the 6-month mortality rate was 22.4%.…”
Section: Discussionmentioning
confidence: 99%
“…PNI, when used as a preoperative pretest, can help predict postoperative mortality as a tool for evaluating nutrition. Taskin et al [ 19 ] reported that in geriatric femur fractures, preoperative albumin, prealbumin, and PNI values were found to be significantly lower in patients who developed mortality compared to those who survived. The authors stated that the cut-off PNI value for predicting mortality in patients with femur fractures was 29, and the 6-month mortality rate was 22.4%.…”
Section: Discussionmentioning
confidence: 99%